DEVELOPMENT OF CREATIVE THINKING OF YOUNGER SCHOOLCHILDREN IN LESSONS OF LABOR TRAINING USING NON- TRADITIONAL MATERIALS - Mirkamalovna, Rustamova Manzura (International Journal of Psychosocial Rehabilitation, 2020)
Significant opportunities in terms of the development of creative thinking open, in our opinion, the lessons of labor training at school. Labor training, like no other activity, imposes multilateral requirements on a person, thereby exerting a versatile influence on the formation of various personality qualities, as well as the development of general and special abilities. In this activity, the process of mastering theoretical knowledge and the acquisition of a certain system of practical skills are harmoniously combined. This article is written about the development of students’ creative abilities in technology classes.